2016
DOI: 10.1007/s00066-016-0973-0
|View full text |Cite
|
Sign up to set email alerts
|

Inclined head position improves dose distribution during hippocampal-sparing whole brain radiotherapy using VMAT

Abstract: Inclining the head position to approximately 11° during HS-WBRT using VMAT improved dose distribution in the planning target volume and allowed lower doses to the hippocampi and optic apparatus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…The method explored here managed to produce a steeper dose gradient in all patients, including those with metastases located in the vicinity of the hippocampi. In spite of the strong dose modulation, the TC, conformity and homogeneity indices for whole brain and metastases obtained in this trial were adequate and comparable with the results of previous studies [ 16 , 30 32 ].…”
Section: Discussionsupporting
confidence: 88%
“…The method explored here managed to produce a steeper dose gradient in all patients, including those with metastases located in the vicinity of the hippocampi. In spite of the strong dose modulation, the TC, conformity and homogeneity indices for whole brain and metastases obtained in this trial were adequate and comparable with the results of previous studies [ 16 , 30 32 ].…”
Section: Discussionsupporting
confidence: 88%
“…However, the availability of tomotherapy is limited, and the treatment planning time is significantly longer. Another possibility to improve the quality of the treatment planning could be an inclined head position [33,34]. In a recently published study, Zheng et al showed feasibility using VMAT and tomotherapy for HT-P and hippocampal axis sparing for cranio-spinal irradiation.…”
Section: Discussionmentioning
confidence: 99%
“…All patients were positioned using a Variable Axis Baseplate ™ (CIVCO Medical Instruments, Kalona, IA, USA). The head was inclined as previously described [ 18 ]. The computed tomography (CT) scans were acquired by using a Brilliance CT Big Bore™ CT simulator (Philips, Cleveland, OH, USA) with a slice thickness of 2 mm.…”
Section: Methodsmentioning
confidence: 99%